Avaliação de um pulverizador e volume ultra baixo e de adjuvantes em caldas fitossanitárias na cultura dos citros - Decaro Junior, Sergio Tadeu [UNESP] (2015)
Sprays in citrus orchards are performed by means of excess of applied volume, which implies in high operational cost and decrease of the competitiveness in this sector. The present work evaluated reductions on the application volume in citrus, employing a conventional sprayer and an ultra low volume sprayer, by means of jets setting and nozzles change. The nozzles named effervescent of the ultra low volume sprayer were assessed on the droplet spectra produced with spraying liquids containing adjuvants in different concentrations, comparing to the pattern water. All the spraying liquids utilized at the field application and at the nozzles evaluation, along with fungicide liquids with mineral oil and manganese sulphate concentrations, were assessed according to different variables. They were surface tension, viscosity, density, pH, conductivity, stability, sprayed droplets diameter, contact angle of droplets and liquid retention on citrus leaves, aiming to identify similarity among the spraying liquids and correlations among variables. From the results, the volume 630 L ha-1, with the conventional sprayer, and the volume 160 L ha-1, with the ultra low volume sprayer, may be adopted for the control of pathogens, on citrus plants, with similar coverage and higher fungicide volume deposited on the leaves in comparison with the volume of 1,200 L ha-1 conventionally practiced. The effervescent nozzle produces very fine droplets, in such a way the use of mineral oil in concentrations higher than 11%, as well as the adjuvant heptamethyltrisiloxane, on recommended dosage, reduce the risk of droplets from drift, whilst the adjuvant phosphatidylcholine favors the production of more fine and uniform droplets. The choice of determined adjuvant must presuppose effect in several variables of the spraying liquid, opting for products with a more pronounced effect on the variable of agronomic interest. The higher was the viscosity, the higher was the ...